Increasing Work Productivity with The Quality of PT. Sari Warna Asli Garment - Wahyudi, Tri Nur; Dzikra, Noor Syahidah Mutiara; Silmi, Vinna Idamatus; Saputro, Kurniawan Ari (Proceedings International Conference on Education Innovation and Social Science, 2022)
The purpose of this study is to test whether the level of work productivity has a relationship with product quality at PT. Sari Warna Asli Garment. The number of samples in this study was 45 employees with a random sampling technique (probability sampling) where the sample selection method for each member of the population had an equal chance of being selected as a member of the sample. Data collection method using questionnaires. The results showed an increase in work productivity carried out at PT. Sari Warna Asli Garment has a moderate degree of correlation or relationship with the quality of the products produced in the company. So that researchers can conclude the level of work productivity in PT. Sari Warna Asli Garment can be improved by the methods and research provided by the company to employees so that there is no decrease in the quality of the products produced.